If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(x + 2) + -2(2x + 1) = 27 Reorder the terms: 7(2 + x) + -2(2x + 1) = 27 (2 * 7 + x * 7) + -2(2x + 1) = 27 (14 + 7x) + -2(2x + 1) = 27 Reorder the terms: 14 + 7x + -2(1 + 2x) = 27 14 + 7x + (1 * -2 + 2x * -2) = 27 14 + 7x + (-2 + -4x) = 27 Reorder the terms: 14 + -2 + 7x + -4x = 27 Combine like terms: 14 + -2 = 12 12 + 7x + -4x = 27 Combine like terms: 7x + -4x = 3x 12 + 3x = 27 Solving 12 + 3x = 27 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + 3x = 27 + -12 Combine like terms: 12 + -12 = 0 0 + 3x = 27 + -12 3x = 27 + -12 Combine like terms: 27 + -12 = 15 3x = 15 Divide each side by '3'. x = 5 Simplifying x = 5
| 8x+100=9-5x | | 8x-x^2+12=0 | | x+4=2x+10-x | | 5(4x-6)=30 | | -.32(.5x-10.3)=0.6x+9.63 | | 2y=(10+2y)-10 | | -4=2x-3 | | 4(9+x)=48 | | 4(9+x)=4 | | 0.5(m-10)=21 | | 3x+6=8x+16 | | 23.00=4g+3.68 | | 0.2w=0.02 | | 48=3(x+2)(x-4) | | 34-(x+8)=9x-4 | | -4m-24=-4(1+6m) | | 25-v-14=9 | | 19=x-5+x | | 3x=68-x | | 16x^3+32x^6+27x^4= | | 6.5=8.9-0.4x | | 0=2z-4 | | 12.44=2g+3.82 | | 6x+2(2x-1)=10 | | .5x+.45(50)=39.5 | | 10.5x=100000 | | 5(6x-6)=60 | | 0.8y+25=-1 | | 6+8q=9+7q | | -7(2x+6)=42 | | (x-10)(x-5)=(x+9)(x+9) | | -6+2x=-6x+34 |